2021
DOI: 10.3389/fpls.2021.664733
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Gene Co-expression Analysis and Metabolites Profiling Highlight the Important Role of ZmHIR3 in Maize Resistance to Gibberella Stalk Rot

Abstract: Gibberella stalk rot (GSR) caused by Fusarium graminearum is one of the most devastating diseases causing significant yield loss of maize, and GSR resistance is a quantitative trait controlled by multiple genes. Although a few quantitative trait loci/resistance genes have been identified, the molecular mechanisms underlying GSR resistance remain largely unexplored. To identify potential resistance genes and to better understand the molecular mechanism of GSR resistance, a joint analysis using a comparative tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 78 publications
(96 reference statements)
0
9
0
Order By: Relevance
“…To identify oxylipins that may explain decreased resistance of zmlox5-3 mutant, we performed oxylipin quantification in the mutant and B73 at different time points upon infection with F. graminearum . To hone-in a subset of oxylipins associated with GSR resistance, we included the GSR resistant inbred line W438 (Sun et al, 2021 ) in the panel subjected to oxylipin profiling. The principal component analysis showed a clear trend of separation between control and infected samples for all three lines.…”
Section: Resultsmentioning
confidence: 99%
“…To identify oxylipins that may explain decreased resistance of zmlox5-3 mutant, we performed oxylipin quantification in the mutant and B73 at different time points upon infection with F. graminearum . To hone-in a subset of oxylipins associated with GSR resistance, we included the GSR resistant inbred line W438 (Sun et al, 2021 ) in the panel subjected to oxylipin profiling. The principal component analysis showed a clear trend of separation between control and infected samples for all three lines.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been established that ZmWRKY83 is a crucial transcription factor for plant disease resistance [41]. Moreover, using integrated gene co-expression analysis and metabolite profiling, it was discovered that ZmHIR3 likely contributes to disease resistance to GSR, probably through the transcriptional regulation of key genes, functional metabolites, and the control of cell death [42].…”
Section: Discussionmentioning
confidence: 99%
“…In rice, the NH1/OsNPR1 paralog can enhance disease resistance and hypersensitivity and participate in cell death [ 76 ]. In maize, ZmHIR3 is a hypersensitive response-related gene that increases resistance to Gibberella stalk rot [ 77 ]. We found that hypersensitive and apoptotic processes are likely involved in the response to RBSDV infections in maize.…”
Section: Discussionmentioning
confidence: 99%